2018
DOI: 10.3389/fmicb.2018.00891
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyletic Nature of Salmonella enterica Serotype Derby and Lineage-Specific Host-Association Revealed by Genome-Wide Analysis

Abstract: In France, Salmonella Derby is one of the most prevalent serotypes in pork and poultry meat. Since 2006, it has ranked among the 10 most frequent Salmonella serotypes isolated in humans. In previous publications, Salmonella Derby isolates have been characterized by pulsed field gel electrophoresis (PFGE) and antimicrobial resistance (AMR) profiles revealing the existence of different pulsotypes and AMR phenotypic groups. However, these results suffer from the low discriminatory power of these typing methods. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 50 publications
10
75
0
Order By: Relevance
“…Moreover, several studies have demonstrated correlations between S. Derby in pigs and humans (80,(82)(83)(84)(85)(86)(87). For example, in Italy, a comparison of the pulsed-field gel electrophoresis (PFGE) profiles of swine and human isolates confirmed a strong correlation between S. Derby isolated from animals in slaughterhouses and those held at lairage for long periods.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, several studies have demonstrated correlations between S. Derby in pigs and humans (80,(82)(83)(84)(85)(86)(87). For example, in Italy, a comparison of the pulsed-field gel electrophoresis (PFGE) profiles of swine and human isolates confirmed a strong correlation between S. Derby isolated from animals in slaughterhouses and those held at lairage for long periods.…”
Section: Discussionmentioning
confidence: 97%
“…Derby, the most prevalent serotype in the panel, and presented a MDR phenotype. Previous studies have suggested that this serotype, commonly found in pig and poultry, is polyphyletic, with certain lineages being primarily recovered from either pig or poultry (Hayward, Petrovska, Jansen, & Woodward, ; Sevellec et al, ). Interestingly, typing of 140 isolates representative of the pork and poultry food sectors in France retrieved in 2014–2015 revealed that while MDR phenotypes (with resistance to amynoglycosides, sulphonamides and tetracycline) were associated with pig‐specific lineages in France, isolates from poultry were typically pansusceptible (Sevellec et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Databases rely on proper serotyping from providing laboratories. Bioinformatic resources are required to analyse WGS data, including analysis pipelines for assembly, annotation, and interpretation of the data, which will require a coordinated international approach (Franz et al., ; Oulas et al., ). Novel O‐ and H‐types continue to be identified, especially for STEC, and there is a requirement for continued database up‐dating and curation for Salmonella and STEC. WGS O‐ and H‐antigen data can be used to define new serotypes that do not match ‘classically defined’ serotypes. WGS‐inferred serotypes can in most instances be compared directly with classical serotyping data ensuring comparability of results between laboratories working following different methods. If WGS‐inferred serotypes of Salmonella and STEC are collected centrally in a timely way, these data could form the basis for a powerful first level detection of clusters in outbreak investigations and source tracing. Identification of subgroups within Salmonella serotypes and discrimination among lineages of polyphyletic serotypes can provide insights into host specificity (Sévellec et al., ). With WGS, control surveillance could be focused on the pathotype concept for STEC considering virulence genes instead of serogroup/serotype (sero‐/pathotype).…”
Section: Assessmentmentioning
confidence: 99%
“…Thus, interpretation of WGS data has to consider the knowledge of the natural mutation rates of the particular pathogen, and its behaviour in the food chain under the specific environmental processing factors (e.g. temperature, pH value, pressure, disinfection procedures) (Besser et al, 2018;Sch € urch et al, 2018). In consequence, this might lead to misinterpretation when epidemiological data of the samples are not sufficiently considered.…”
Section: Value Of Wgs For Food-borne Outbreak Detection and Trace-bacmentioning
confidence: 99%